Mangroves as a Nature-Based Solution for Coastal Water Eutrophication in Macao Sar China - Lai, Wai Ian (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Designing an Optimized Constructed Wetland System with Circular Sustainability for Wastewater Treatment in Macao - Lei, Micaela (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Guidelines for an Oriented Organic Waste Valorization Strategy for Macao - Lei, Man Sao (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Adoption of Best Practices for Municipal Solid Waste Recycling Management in Macao - Li, Man Ho (University of Saint Joseph, 2017)
Municipal Solid Waste (MSW) is associated with industrialization, urbanization, and a modern economic development, covering several origins such as households and similar waste streams from commerce and trade. Inappropriate waste management impacts human health and the environment negatively, but also the economy and society in general. Waste is today also seen more and more as resource itself. The world trend is to move from mere waste management to a consistent form of resource management within a circular economy, e.g. in form of an Integrated Waste Management System (IMWS). Concerning Macao, MSW is being transported to the Macao Refuse Incineration Plant for thermal treatment with energy recovery. For 2014 and 2015, the amount of waste transferred to the Macao Refuse Incineration Plant for treatment shows a strong yearly increase (11.3 %) being expected to reach or even exceed the maximum allowable waste handling capacity in near future. Alternative methods for waste treatment and valorization are necessary for an effective and sustainable waste management system in Macao. In this research, three case-studies were carried out to analysis real case scenarios that are considered examples of well-functioning MSW management. They were: 1) LIPOR (Portugal); 2) Resinorte (Portugal) and 3) Hong Kong. A questionnaire was prepared and distributed to Macao residents in order to understand their perceptions and views on the existing solid waste recycling in Macao. According to the results of the case-studies and questionnaire, based on the “Polluter Pays Principle” and “Producer Responsibility Scheme”, the main objective of this research is to suggest best practices for waste recycling and management in Macao for the Government, Company, Recycling Trade Participator and the Individual Level
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Green Roof, Nature-based Solutions, Biodiversity, Sustainability, Macao SAR, China - Lei, Man Sao (University of Saint Joseph, 2023)
According to the United Nations (UN) World Urbanization Prospects 2018, cities are growing in both size and number, posing challenges for sustainable development. With urbanization, the increase of impermeabilization and landscape fragmentation urges for territorial planning and resources management. To promote resilient and resourceful cites, strategic planning where nature-based solutions (NBS) are included into the built environment, counteracting the negative effects of urbanization through the provision of ecosystem services, should be considered. Green roofs (GR) are an example of NBS that provide a panoply of ecosystem services at the level of the building and city, besides contributing for climate change mitigation and adaptation. This NBS can be included in the urban planning agenda in the new building or as a retrofit solution in the existing built environment. Macao SAR (here mentioned as Macao) is the second more densely populated city in the world, according to the UN Department of Economic and Social Affairs Population Division. The present study aims to assess the inclusion of GR in Macao and assess the ecosystem services that they may provide in a holistic approach aligned with the city’s sustainable development. For this purpose, an extensive GR implemented in Taipa Island of Macao was monitored in terms of associated biodiversity and carbon cycle assessment. Further on, it was carried out a comparison between this GR and a conventional roof (CR) in terms of surface thermal buffering. The results of this study have shown to be very promising in terms of the applicability of GR in Macao and on the relevant ecosystem services that they can provide. First, data loggers were installed in the GR and CR to assess the impact on temperature mitigation. The GR had a significant effect in decreasing and buffering temperature at the surface, with temperatures of 35.6 ºC in the GR substrate comparing with temperatures of 57.7 ºC in the CR surface. The results show that GR can be a cost-efficiency strategy to reduce heating of buildings and their associated environmental and economic costs with cooling. Second, the biodiversity of plants and animals was assessed using a combination of methods. It was observed a high level of biodiversity under a low maintenance and low disturbance of GR vegetation, with 23 species of plants and 34 species of animals identified. This shows that GR can contribute to increase biodiversity in cities. Third, an experiment was run with leaf litter bags to investigate the role of macrofauna (e.g., insects) in the decomposition of organic matter. With macrofauna activity, the decomposition rate increased 17 % when compared to decomposition rates without macrofauna, suggesting that the animals harboured in GR, in particular insects, play a key role in organic matter decomposition and thus on the carbon cycle in cities. This work is, to our knowledge, the first empirical GR study in Macao. The results support the application of GR in Macao for temperature mitigation, biodiversity increase and carbon sequestration, promoting the integration of this NBS in the future urban planning and policy of the city. More generally, the work supports the use of GR as an important NBS to mitigate the impact of climate change in urban settings
Keywords: Biodiversity; China; Green Roof; Macao SAR; Nature-based Solutions; Sustainability

LIFE CYCLE ASSESSMENT OF CONSTRUCTED WETLAND SYSTEMS FOR TOURISM UNITS WASTEWATER TREATMENT - Lo, Weng In (University of Saint Joseph, 2022)
With water being an essential for life on Earth, it is vital to preserve it and regenerate it, in order to be available for a myriad of uses. Though many types of wastewater management and treatment are available, most rely on high energy input and are therefore not ideal for many circumstances. Constructed wetlands (CW) are an alternative nature-based solution to be applied to wastewater treatment. This study undertakes a Life-Cycle Assessment (LCA) of a CW as a means of wastewater treatment and aims to understand how these systems can be an environmentally conscious alternative. The CW under study is located in a rural mountain area in the north of Portugal. Receives wastewater from a tourism unit and operates with horizontal subsurface. The LCA analyses the CW through the construction, operation (treatment), and composting phases. This approach allows the entire scope of the life cycle to be included, of which, the composting phase has been absent in similar LCA previously undertaken. Analysis focuses on the impact categories: Ozone Layer Depletion Potential, Global Warming Potential, Acidification Potential, Eutrophication Potential and Human Toxicity Potential. Of the five categories, none increase during the treatment phase, and indeed, Acidification Potential, Eutrophication Potential, and Human Toxicity potential all decrease. Ozone Layer Depletion Potential and Global Warming Potential increase significantly during the construction and composting phases respectively. Both can be rationalized, with the former being a result of heavy diesel machinery use in construction and the latter a natural byproduct of composting. The results are net positive and display the ability for CW as a low energy wastewater treatment which can limit environmental impact by choice of construction and composting methodology
Keywords: Lifecycle assessment; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; constructed wetland; wastewater treatment

Nature-Based Solutions for Environmental Education in the East Asian Context - Tagulao, Karen Araño (Enhancing Environmental Education Through Nature-Based Solutions, 2022)
Environmental education (EE) has long been practiced worldwide, while Nature-based solutions (NBS) is a relatively new concept. This chapter aims to provide an overview of the EE and NBS practices in East Asia and evaluate how these two valuable applications can be used concurrently. East Asia has a well developed environmental education (EE) programs and activities, both in formal and informal education. These ranges from developing green schools and campuses to establishing policies and acts. While EE has been actively practiced for decades in the region, the adoption of NBS to address environmental and societal challenges is limited. The educational benefits and opportunities from NBS are also lacking. Although there are some projects that can be classified as NBS, like the use of wetlands for wastewater treatment, they are not clearly categorized as one. These projects are also not integrated into environmental education programs. Considering this, the region should develop innovative environmental education programs for schools, universities and communities, that integrate NBS projects. Integrating the two together will boost the effectiveness of environmental education in raising environmental awareness and changing the environmental attitude and behavior of people, which will also help address societal issues.
Keywords: Environmental awareness; Environmental policies/acts; Green schools; Green universities; Sponge cities; Wetlands

Mangroves as ecosystem services providers in an urban context: case study of Macao, SAR China - Vanessa, W. L.; Calheiros, Cristina S. C.; Tagulao, Karen (University of Porto, 2020)

Mangroves as nature-based solution for coastal water eutrophication in Macao, SAR China - Vanessa, W. L.; Calheiros, Cristina S. C.; Tagulao, Karen (Blue Think Conference: Share Science, Spread Knowledge, 2020)

Mangrove Conservation in Macao SAR, China: The Role of Environmental Education among School Students - Tagulao, Karen Araño; Bernardo, Allan B. I.; Kei, Loi Hoi; Calheiros, Cristina Sousa Coutinho (International Journal of Environmental Research and Public Health, 2022)
Mangrove forests are one of the most ecologically valuable ecosystems in the world and provide a wide variety of ecosystem services to coastal communities, including cities. Macao, a highly urbanized coastal city located on the southern coast of China west of the Pearl River, is home to several species of mangroves with many associated flora and fauna. Mangrove forests in Macao are vulnerable to threats due to pressure from rapid and massive urban developments in the area, which led to mangrove loss in the past decades. To address this issue, the local authorities established special Ecological Zones for the management of the local mangroves. To reinforce local conservation efforts, educating the local population about the value of mangroves, especially school students, is of utmost importance. To evaluate the impact of environmental education activities on the environmental orientation, knowledge, and values of students toward mangrove conservation in Macao, a quasi-experimental study was undertaken. The effectiveness of a mangroves exhibition and field visit were evaluated using the New Environmental Paradigm (NEP) Scale—Macao version in a group of local school students who participated in the activities. Overall, the results provided consistently positive evaluations of the impact of the environmental education program. The strongest improvements were found in the students’ pro-environmental orientations, knowledge about mangroves, and value for environmental protection.
0 citations (Crossref) [2023-03-15] Number: 6 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: NEP-New Ecological Paradigm; conservation; environmental orientation; environmental protection; urban mangroves